2022
DOI: 10.3390/app12147243
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of the Efficiency of LSTM-Based Motion Classification Algorithms Using a Single Accelerometer

Abstract: Inertial sensors are widely used for classifying the motions of daily activities. Although hierarchical classification algorithms were commonly used for defined motions, deep-learning models have been used recently to classify a greater diversity of motions. In addition, ongoing studies are actively investigating algorithm efficiency (e.g., training time and accuracy). Thus, a deep-learning model was constructed in this study for the classification of a given motion based on the raw data of inertial sensors. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…It has a unique structure that enables it to perform better than general recurrent neural networks, especially in tasks such as autonomous speech recognition [35]. LSTM is not limited to speech-recognition tasks; it can also be applied in other areas, such as predicting human decisions [36], exoskeleton control, and posture-change detection for other equipment [37][38][39]. When the human body performs a posture change (whether it is wearing an exoskeleton or there is human-computer interaction), there is a linkage and correlation between each of the joints of lower limbs, and there is also continuity between and memory of various movements.…”
Section: Introductionmentioning
confidence: 99%
“…It has a unique structure that enables it to perform better than general recurrent neural networks, especially in tasks such as autonomous speech recognition [35]. LSTM is not limited to speech-recognition tasks; it can also be applied in other areas, such as predicting human decisions [36], exoskeleton control, and posture-change detection for other equipment [37][38][39]. When the human body performs a posture change (whether it is wearing an exoskeleton or there is human-computer interaction), there is a linkage and correlation between each of the joints of lower limbs, and there is also continuity between and memory of various movements.…”
Section: Introductionmentioning
confidence: 99%
“…And one of the main difficulties is the precise perception of hand motion [27], which requires a robust and reliable sensing system. Many wearable devices have been extensively validated for their effectiveness in human-computer interfaces, robot control, and exoskeleton intent control research [28][29][30][31]. Wearable data gloves have also been proven to enable continuous control of bionic hands, and numerous related studies have confirmed the stability and reliability of this control method [32,33].…”
Section: Introductionmentioning
confidence: 99%